Expression and clinical significance of NGAL/NGALR in lupus nephritis - ZENG Xing-ruo; FANG Xun; LIU Chang-xuan; LOU Mei-yu; CHEN Wen-li (Linchuang shenzangbing zazhi)
Objective To investigate the expression and clinical significance of NGAL/NGALR in lupus nephritis( LN). Methods Eighty-four patients with systemic lupus erythematosus( SLE) were selected in this study,and divided into LN group and non-LN group. The normal tissues adjacent to carcinoma of kidney were chosen as controls,resected during the operation in Department of Urology,the Central Hospital of Wuhan. Enzyme-linked immunosorbent assay was used to detect the NGAL/NGALR expression level in serum and urine of the patients with or without lupus nephritis. Immunohistochemical method was used to detect the expression differences of NGAL/NGALR in lupus nephritis tissue and normal renal tissue. SLEDAI score was recorded by the SLEDAI-2000 scoring system( version 1985). SPSS 19. 0 software was applied for data analysis,t test for two-group comparison,variance analysis for multi-group comparison,and spearman rank correlation analysis for correlation analysis. Results The expression levels of NGAL/NGALR in lupus nephritis patients were significantly higher than in those without lupus nephritis in both serum and urine. The expression levels of NGAL/NGALR increased significantly in lupus nephritis tissues.Conclusions NGAL and NGALR may be closely related to the occurrence/development and the activity of lupus nephritis,which can assist the clinical diagnosis,and may be expected to become the new targets for therapy of lupus nephritis.